UV irradiation-induced apoptosis leads to activation of a 36-kDa myelin basic protein kinase in HL-60 cells. - Lu, M L (1996)
UV irradiation induces apoptosis (or programmed cell death) in HL-60 promyelocytic leukemia cells within 3 h. UV-induced apoptosis is accompanied by activation of a 36-kDa myelin basic protein kinase (p36 MBP kinase). This kinase is also activated by okadaic acid and retinoic acid-induced apoptosis. Irrespective of the inducing agent, p36 MBP kinase activation is restricted to the subpopulation of cells actually undergoing apoptosis. Activation of p36 MBP kinase occurs in enucleated cytoplasts, indicating no requirement for a nucleus or fragmented DNA in signaling. We also demonstrate the activation of p36 kinase in tumor necrosis factor-alpha- and serum starvation-induced cell death using the human prostatic tumor cell line LNCap and NIH 3T3 fibroblasts, respectively. We postulate that p36 MBP kinase is a common component in diverse signaling pathways leading to apoptosis.